PERAN KEPOLISIAN DALAM MELAKUKAN BIMBINGAN KONSELING TERHADAP ANAK BERHADAPAN HUKUM - Muharomah Fajarini Muharomah Fajarini (UIN Kiai Haji Achmad Siddiq Jember, 2022)
This study explains the role of the police in providing counseling for children facing the law, and the obstacles they face. This study uses a statutory approach, as well as a case approach with regard to the role of the police in providing counseling for children in conflict with the law. The results of this study are that the police in providing counseling guidance to children facing the law have been carried out according to what is mandated by Law Number 2 of 2002 concerning the Police, but there are still people who are not satisfied with the performance of the police, especially the victims. Constraints faced by the police in providing counseling guidance to children in conflict with the law are the stigma of the community on the performance of the police in handling children's cases, the lack of socialization of Law Number 2 of 2002 concerning the Police, the strong desire of victims to provide legal sanctions against perpetrators